(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to shed light on the concept of poor financial investments and state the principles and find indicators to help identify its elements of accounting disclosure, in light of local and international rules and accounting standards, and to show Iraqi commercial banks’ commitment to disclose its poor financial investments in the financial statements. In order to achieve the objectives of the research, the financial statements of two banks - the two banks trident operating in the Iraqi banking environment- were studied. The research concluded that the research sample banks did not measure and disclose poor financial investments accounts in the financial statements, and the lack of appropriate indicators of measurement and disclosure of accounting for poor financial investments in the financial reports of these banks to meet the needs of beneficiaries